2022
DOI: 10.1371/journal.pone.0262555
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of pulsed electric field for the rupture of giant vesicles with various surface charges, cholesterols and osmotic pressures

Abstract: Electropermeabilization is a promising phenomenon that occurs when pulsed electric field with high frequency is applied to cells/vesicles. We quantify the required values of pulsed electric fields for the rupture of cell-sized giant unilamellar vesicles (GUVs) which are prepared under various surface charges, cholesterol contents and osmotic pressures. The probability of rupture and the average time of rupture are evaluated under these conditions. The electric field changes from 500 to 410 Vcm-1 by varying the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…Vesicles such as GUVs with diameters �10 μm were used for examining and revealing the pore formation event in the membrane due to antimicrobial peptides [28][29][30], mechanical tension of membrane [31,32], osmotic pressure effect [33,34], rupture of membrane comprising polar lipids extracted from E. coli [35], electroporation [36], and to study the size distribution of self-assemble vesicles [37]. The real-time measurement of the shape and physical properties of a 'single GUV' under physiological condition can be performed using optical microscopes.…”
Section: Introductionmentioning
confidence: 99%
“…Vesicles such as GUVs with diameters �10 μm were used for examining and revealing the pore formation event in the membrane due to antimicrobial peptides [28][29][30], mechanical tension of membrane [31,32], osmotic pressure effect [33,34], rupture of membrane comprising polar lipids extracted from E. coli [35], electroporation [36], and to study the size distribution of self-assemble vesicles [37]. The real-time measurement of the shape and physical properties of a 'single GUV' under physiological condition can be performed using optical microscopes.…”
Section: Introductionmentioning
confidence: 99%
“…The researchers used cholesterol to prepare giant unilamellar vesicles, and found that the rupture of the plasma membrane under the electric field would be hindered by cholesterol. 37,[58][59][60] Most simulations suggested that cholesterol delayed the occurrence of electroporation, but the effect of cholesterol on the perforation propensity of lipid bilayer was strongly dependent on the structure of lipids. Mauroy et al reported that the decrease of poration propensity in POPC phospholipid was due to the increase content of cholesterol, 61 but Portet found that the increasing cholesterol accelerated the occurrence of electroporation in dioleoylphosphocholine (DOPC) vesicles.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers used cholesterol to prepare giant unilamellar vesicles, and found that the rupture of the plasma membrane under an electric field would be hindered by cholesterol. 37,58–60 Most simulations suggested that cholesterol delayed the occurrence of electroporation, but the effect of cholesterol on the propensity for perforation of the lipid bilayers was strongly dependent on the structure of the lipids. Mauroy et al reported that the decrease in the propensity for poration for the POPC phospholipid was due to the increased content of cholesterol, 61 but Portet found that increasing the content of cholesterol accelerated the occurrence of electroporation in dioleoylphosphocholine (DOPC) vesicles.…”
Section: Introductionmentioning
confidence: 99%